Bereaved relatives' quality of life before and during the COVID-19 pandemic: Results of the prospective, multicenter, observational eQuiPe study. (September 2021) - Ham, Laurien; Fransen, Heidi P; van den Borne, Ben; Hendriks, Mathijs P; van Laarhoven, Hanneke WM; van der Padt-Pruijsten, Annemieke; Raijmakers, Natasja; van Roij, Janneke; Sommeijer, Dirkje W; Vriens, Birgit EPJ; van Zuylen, Lia; van de Poll – Franse, Lonneke
Background: The death of a loved one is considered as one of the most stressful life events. During the COVID-19 pandemic, grief processes are potentially affected by measures such as social distancing and self-quarantine. Aim: The aim of this study was to give insight in the impact of the COVID-19 pandemic on quality of life, social support, and self-care of bereaved relatives of people with advanced cancer in order to evaluate whether care for bereaved relatives during the COVID-19 pandemic should be improved. Design: A cross-sectional analysis using data from bereaved relatives of a prospective, longitudinal, multicenter, observational study on quality of care and quality of life of people with advanced cancer and their (bereaved) relatives (eQuiPe). Setting/participants: Quality of life, social support, and self-care of bereaved relatives who completed a questionnaire within 3–6 months after their relative died during COVID-19 (April-November 2020) were compared with bereaved relatives who completed this questionnaire pre-COVID-19 (April-November 2019). Results: Ninety-one bereaved relatives were included in the analysis, 44 bereaved relatives completed the questionnaire pre-COVID-19 and 47 during COVID-19. The median age of the participants was 65 (IQR = 14) years and 58% were female. There were no significant differences between the pre-COVID-19 and during COVID-19 bereaved relatives in quality of life (68 vs 69), social support (17 vs 18), and self-care (20 vs 19). Conclusions: On the short-term, the COVID-19 pandemic did not have significant impact on bereaved relatives' wellbeing. However, long-term impact of the pandemic on their wellbeing should be assessed.